A 3-year retrospective study of unintended pregnancy in a developed multi-ethnic Asian community: A call for better healthcare system for family planning - Quak, Xin En Stephanie; Sultana, Rehena; Aau, Wai Keong; Goh, Chin Chin; Tan, Ngiap Chuan (Frontiers in Public Health, 2022)
Background Women of childbearing age may face unintended pregnancy (UP). They are usually referred by primary care professionals (PCPs) to gynecologists to manage their UP in countries where abortion is legalized. The study aimed to determine the prevalence, demographic profiles, and associated factors of women in a developed community seeking referrals from PCPs for their UP. Methods The sociodemographic and clinical data were extracted from the electronic medical records of pregnant multi-ethnic Asian women at eight Singapore public primary care clinics from July 2017 to June 2020. Their demographic profiles were reviewed and compared among women of different age bands using appropriate statistical tests. Logistic regression was used to identify the factors associated with UP referrals. Results Among 9,794 gravid women, 974 of them requested gynecologist referrals to terminate UP over the 3-year period, constituting a prevalence of 9.94%. The mean age of women requesting such referrals was 29.7 ± 7 years. There were 10.7% with more than one prior unintended pregnancy and 15.7% were foreigners. The majority of these women were married, neither required social assistance nor had comorbidities. Only 2.9% of them were known to be prescribed contraceptives. A multivariable logistic regression analysis showed that women of Indian ethnicity, single, aged below 20 years and above 40 years, were more likely to request referrals for UP. Conclusion One in 10 gravid women had sought referrals for UP, especially adolescents and older women, and Indian ethnicity. An accessible community-based healthcare service to educate and counsel women on family planning is urgently needed to reduce the incidence of UP.